Bibliography: the Conflict in Libya - Teiner, David (Perspectives on terrorism, 2022)
This bibliography contains books, edited volumes, journal articles, book chapters, theses, grey literature, and other resources on the ongoing conflict in Libya. Most of the included literature was published since Mu’ammar al-Qaāfī’s removal in 2011. Many of the publications included focus on the Libyan revolution, protest movements, the emergence of militias, the Islamic State in Libya, and the successes and failures of international interventions in the country’s conflicts. Earlier publications analyzing political, social, economic, or religious developments, that help to understand the dynamics of the present conflict, are also included. The literature has been retrieved manually and should thus not be considered exhaustive.